Pengaruh Free Cash Flow, Net Profit Margin, dan Kepemilikan Asing Terhadap Pertumbuhan Laba: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Farmasi dan Kimia yang Terdaftar di BEI Tahun 2019-2023 - Vanessa Auraestu Noviandari; Tri Cahyono, Yuli (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the effect of Free Cash Flow (FCF), Net Profit Margin (NPM), and Foreign Ownership on profit growth in pharmaceutical and chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach with a positivist paradigm was employed, using secondary data derived from annual reports of companies that met purposive sampling criteria, including consistent IDX listing, financial reports in rupiah, consecutive positive profits, and availability of data related to the research variables. Data analysis methods included descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), and multiple linear regression analysis. The results indicate that FCF and Foreign Ownership have no significant effect on profit growth, while NPM has a significant positive effect. These findings suggest that profitability is a key factor influencing the profit growth dynamics of companies within the pharmaceutical and chemical manufacturing sub-sector.